2011
DOI: 10.1159/000335541
|View full text |Cite
|
Sign up to set email alerts
|

Progression from Amnesic Mild Cognitive Impairment to Alzheimer’s Disease: <i>ESR1</i> and <i>ESR2</i> Polymorphisms and <i>APOE</i> Gene

Abstract: Background: Many genes have been studied to determine how they might be involved in Alzheimer’s disease (AD). Estrogens have a protective effect in the central nervous system. The mechanisms of action of estrogens are mediated by two estrogen receptors (ERs), ERα and ERβ. Thus, these genes could also play a role in the progression of amnesic mild cognitive impairment (MCIa) to AD. The aim of this study was to examine the role of ER single nucleotide polymorphisms (SNPs) as a risk factor for MCIa, as well as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 140 publications
0
10
0
Order By: Relevance
“…A cohort study performed in 79 amnestic mild cognitive impairment (MCIa) patients and 144 healthy controls examined the association between the ERβ SNP rs4986938 and the development of MCIa as well as the interaction between rs4986938 and APOE4 in the progression of AD. The investigators reported that the presence of the APOE4 allele, and not the alleles of the ERβ SNP, is a risk factor for the conversion of MCIa to AD (Elcoroaristizabal Martin et al, 2011). Later, the same investigators conducted a case-control study that examined the association between rs4986938 and the risk of MCIa or AD and no association was found (Fernandez-Martinez et al, 2013).…”
Section: Erβ Polymorphisms In Admentioning
confidence: 99%
See 1 more Smart Citation
“…A cohort study performed in 79 amnestic mild cognitive impairment (MCIa) patients and 144 healthy controls examined the association between the ERβ SNP rs4986938 and the development of MCIa as well as the interaction between rs4986938 and APOE4 in the progression of AD. The investigators reported that the presence of the APOE4 allele, and not the alleles of the ERβ SNP, is a risk factor for the conversion of MCIa to AD (Elcoroaristizabal Martin et al, 2011). Later, the same investigators conducted a case-control study that examined the association between rs4986938 and the risk of MCIa or AD and no association was found (Fernandez-Martinez et al, 2013).…”
Section: Erβ Polymorphisms In Admentioning
confidence: 99%
“…One major factor that may have contributed to the disparities among studies could be the composition of the study population. One common feature shared in 4 of the 5 reports that failed to find an association is that those studies were all based on a mixed population of both genders (Elcoroaristizabal Martin et al, 2011; Fernandez-Martinez et al, 2013; Ryan et al, 2014). In contrast, of the 8 studies that showed a positive result, 7 studies were either conducted only in women (Dresner-Pollak et al, 2009; Janicki et al, 2014; Luckhaus et al, 2006; Ryan et al, 2013; Zhao et al, 2011c) or stratified by gender (Pirskanen et al, 2005; Yaffe et al, 2009), and all showed a significant association between ERβ polymorphisms and AD susceptibility in women.…”
Section: Erβ Polymorphisms In Admentioning
confidence: 99%
“…Some studies show such a relationship while others do not. In the study of Elcoroaristizabal et al [32] an association between the APOE ε4 allele and amnesic mild cog-nitive impairment was found while no relation to cognition was observed for ESR1 polymorphisms in elderly women. In contrast, in the same study the polymorphisms within the ESR2 gene were associated with lower cognitive performance [30].…”
Section: Discussionmentioning
confidence: 93%
“…As one of NR family member, estrogen receptor α (Erα, P03372), encoded by the ERS1 gene, is highly expressed in brain regions especially the hippocampus and hypothalamus which are associated with memory and cognitive performance [ 25 27 ]. ERα is activated by binding with estrogen and estrogen-ERs has been proposed to partake in cholesterol metabolism and Aβ accumulation in brains from LOAD patients [ 28 ].…”
Section: Discussionmentioning
confidence: 99%